Examining Social Media Thumbnails and Posts: A Critical Analysis of Kite String Incidents and Road Safety in Pakistan - Anwar, Adnan Ali; Noor, Rabia (Annals of Human and Social Sciences, 2025)
This study explores the semiotics and discourses surrounding kite flying accidents, focusing on the impact of YouTube thumbnails and AI-generated images on perceptions of safety and cultural significance. Kite flying poses hazards, particularly from kite strings in South Asia. Visual media often sensationalize these dangers, influencing public opinion and safety narratives. The study employs social-semiotic discourse analysis to examine various images and thumbnails, identifying key themes such as social responsibility, freedom, and danger. Findings indicate that sensationalized imagery and language can distort truth, leading to misinformation. This creates tension between the enjoyment of kite flying and safety concerns, highlighting media's role in shaping societal attitudes and regulatory demands. The study advocates for ethical media consumption that balances cultural heritage with safety, emphasizing the need for critical engagement with visual narratives to foster informed discussions and appropriate safety measures.